Kasus Wang Renshu: Sebuah Kegagalan Diplomasi RRC terhadap Indonesia - Muas, Tuty Enoch (UI Scholars Hub, 2023)
The Chinese-Indonesian relations in 1951 was in tension due the actions of Ambassador Wang Renshu. As China was not favored in the international arena for its communist stand, the Chinese citizens in Indonesia became important factor in the relations between China and Indonesia where they were divided into taking side with either the communists or the capitalists. Wang Renshu, a senior member in the China Communist Party, has recruited between six and seven hundred thousand Indonesians of Chinese ancestry to adopt Chinese citizenship, of which it became a threat to the Chinese-Indonesian diplomatic relations. The withdrawal of Ambassador Wang Renshu marked the failure of the Chinese- Indonesian diplomatic relations.